N-glycosylation patterns of plasma immunoglobulin G in anti-synthetase syndrome disease - Zhao, Jing; Li, Yanhong; Ling, Yingying; Wu, Tong; Wu, Yinlan; Tan, Chunyu; Cheng, Lu; Huang, Deying; Liu, Yi; Zhang, Yong (Frontiers in Immunology, 2025)
IntroductionAnti-synthetase syndrome (ASS) is a subtype of idiopathic inflammatory myopathy (IIM) characterized by characteristic rash, myositis, and interstitial lung disease (ILD). The etiology of ASS is unknown, and patients have a poor quality of life and are prone to pulmonary infection. Recent studies have elucidated the potential role of abnormal glycosylation of immunoglobulin G (IgG) in the pathogenesis of autoimmune diseases. However, the pattern of patient-specific IgG N-glycosylation in ASS has not been fully elucidated.Methodsthe GlycoQuant method was used to quantify the intact N-glycopeptides of IgG from 30 ASS patients and 30 healthy controls (HCs). Results and DiscussionThirteen differentially expressed intact N-glycopeptides were identified (p<0.05). Notably, we observed increased fucosylation (p<0.0001) and decreased N-acetylneuraminic acid (p<0.05) in ASS patients. In addition, specific glycosylation patterns correlated with lung function parameters. Our study revealed the IgG glycosylation profile in ASS patients and provided a valuable reference for further investigation of its potential diagnostic and prognostic applications.